Internet Addiction and Its Association with Anxiety and Depression Among Medical Students of Andhra Pradesh - Dr Sagar R; Dr. Niranjan Kumar Chanamala; Loukya G; Dr. U Raghava Rao; Dr Ramya Rachamanti (International Journal of Pharma and Bio Sciences, 2024)
Internet usage has increased over the past couple of years and is significantly higher among medical students. Estimating the prevalence of Internet addiction and psychological problems among medical students and studying its association with psychological distress can give new evidence in this domain. This study was conducted in various Medical Colleges in Andhra Pradesh. It was a crosssectional study. All parameters were collected at a single point in time. The study was conducted from September 2023 to November 2023 (3 months). A convenience sampling method was used. 240 medical students from various Medical Colleges in Andhra Pradesh were used. Most of the students were from government medical colleges. Females were more compared to males. Most of the students uses the internet for 2 to 4 hours. 28% of students use the internet for 4 to 6 hours. 20% of students use internet for more than 6 hours. 13% of students use internet for less than 2 hours. Most of the students have been using the internet for the last 4 years. The mean number of years of internet usage was 4.23+ 2.52 among the students. Internet addiction prevalence rate was 56.25%. The prevalence of depression and anxiety was 49.17%. 63.3% had no anxiety, 19.6% had minimal to mild anxiety, 10% had moderate to marked anxiety, and 7.1% had severe anxiety. The current study done among 240 medical students proved that there is a high prevalence of internet addiction among medical students, and there is a significant positive correlation between internet addiction and anxiety and depression. A holistic approach is needed to limit medical students’ Internet use. Educating parents, professors, and policymakers about the adverse consequences of Internet addiction helps reduce deleterious consequences on mental health.